Nitrification inhibitor promotes fertilizer N stabilization in soil as organic forms during a growing season of maize: a field 15N tracer study - Quan, Zhi; Li, Shanlong; Liu, Dong; Liu, Chang; Xun, Zhifeng; Chen, Xin; Fang, Yunting (Frontiers in Soil Science, 2025)
There is limited knowledge regarding the impact of nitrification inhibitors (NIs) and straw application on fertilizer N retention and in-season release. We conducted a trial to study the transformation of 15N-labeled urea in soils during the growing season of maize. To facilitate multiple destructive samplings throughout the season, we utilized a larger plot (25 m2) and a lower abundance 15N-fertilizer (1.193%) than usual. Soil extractable mineral N, mineral fixed ammonium, and organic N (ON) recovered 20 ± 21% (mean ± standard deviation), 6 ± 5%, and 25 ± 6% of the applied fertilizer N across three sampling stages of the growing season. On average, the bioavailability of fertilizer N in extractable mineral form was four times higher than that of mineral fixed ammonium. In contrast, fertilizer-derived ON represented a relatively stable N pool, maintaining high content throughout the growing period and becoming the major form (82%–93%) in the pool of total soil 15N at the physiological maturity stage of maize. Moreover, the co-application of nitrapyrin (a type of NI) significantly promoted fertilizer N storage in the ON form while the effect of straw was not significant. In conclusion, the NI-induced promotion of fertilizer-derived ON likely plays a critical role in storing fertilizer N for subsequent cultivations, rather than providing N nutrients for crop uptake during the current season.